Linguocultural Studies of Popularity: Semantic Specificity of Lexicalization of the Concepts of Professional Demand and Success in the Russian Language - K. S. Bakirova; R. A. Bakirov (Концепт: философия, религия, культура, 2024)
The study of the process of lexicalization of concepts is relevant in connection with the need to systematize knowledge about the development of language, taking into account the transformation and renewal of culturally specific concepts. This article aims to clarify the available data on the semantic field of the concept popularity in the given context. Achieving this goal requires, firstly, to establish a range of concepts that form the basis of the semantic field of popularity; secondly, turning to the history of the formation of the semantic certainty of this range of concepts; thirdly, analyzing the lexical meanings of these concepts using quantitative and qualitative methods, including the methods of corpus linguistics; fourthly, establishing the semantic relationships between these concepts, as well as the specifics of their ability to reflect the changes in the world of culture. The semantic specificity of concepts related to popularity in the prism of personal success is examined using specific examples related to the development of the Russian language. The materials of this study were original and translated works containing the lexical units in question. The authors (writers, scientists and philosophers) were selected due to their influence on the development of the concept of popularity in Russian culture. Special attention is given to the data from the National Corpus of the Russian Language. Using the methods of comparative analysis and contextual definition, as well as the analysis of dictionary definitions and contexts of their use. Concepts such as praise, admiration, reputation, fame, glory, celebrity and popularity were all considered. From the linguacultural point of view, a connection between such concepts as popularity and fame is established. A deeper linguistic analysis of the group of concepts under study reveals their characteristic semantic relations. In particular, vector semantic models confirm the close connections between the lemmas success, demand and recognition. In most cases, quasi-synonyms for popularity are fame and success. It is shown how the commercial aspects of these concepts are actualized in the journalistic field (using the example of the news corpus). As a result, it is suggested that the concept of popularity be considered as a complex name of this semantic field. This term names the cultural phenomenon of interest of a wide group of the population to an individual, who is in demand in a specific historical period. The authors conclude that in the information society, this phenomenon acquires features of manipulativeness, which opens up new facets of the concept of popularity.